GrameStation: Specifying Games with Graphs - Silva Junior, Braz Araujo da; Cavalheiro, Simone André da Costa; Foss, Luciana (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2021)
This paper presents a platform for creating games using graphs. The proposed game engine is based on a mathematical formalism called Graph Grammar. It aims to rescue, within computer science education, the stage of specification, that precedes programming. The proposal is aligned to the trends of the problem-solving focus, development of computational thinking, use of visual languages, game-related environments and the maker movement. The structure of the platform and the creation/execution of an example game are described and a brief discussion about specification in computer science education is given.